Antimicrobial and antioxidant activities of leaves and roots of Centella asiatica / Zarina Sarkawi - Sarkawi, Zarina (2015)
Centella asiatica (C asiatica) or locally named as 'pegaga' in Malaysia, belongs to the family Umbelliferare. It is known to have many medicinal benefits and all parts of this plant can be utilized for medicinal used. This study was conducted to determine the antimicrobial and antioxidant activities of the leaves and roots of Centella asiatica. The plant was disintegrated to two part which were leaves and roots and extracted in ethanol for antimicrobial activities against Staphylococcus allreus (ATCC 25923) and methanol extraction for antioxidant activities. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of Centella asiatica leaves and roots extract were determined by broth dilution method against Staphylococcus allreus (ATCC 25923). Antimicrobial sensitivity testing also done using five different concentration of the extract which were 500 mg/ml, 250 mg/ml, 150 mg/ml, 75 mg/ml and 37.5 mg/ml and the antioxidant activities of Casiatica leaves and roots extract were determined by DPPH radical scavenging assay. The Casiatica leaves and roots extract showed MIC and MBC value at concentration of 150 mg/m!. For antimicrobial sensitivity testing the zone of inhibition of the Casiatica leaves extract was greater than Casiatica roots extract. The leave extract gave zone of inhibition range about 10 mm to 12 mm at the concentration of 500 mg/ml and 8 mm to 10 mm at the concentration of 250 mg/m!. There were no zone of inhibition observed on the leave extract at the concentration of 150, 75, 37.5 and mg/m!. The roots extract of the Casiatica only showed the zone of inhibition at the concentration of 500 mg/ml range about 8 mm to 10 mm. There were no zone of inhibition observed on the roots extract at the concentration of 250, 150, 75 and 37.5 mg/m!. The positive control (Gentamicin 30llg) showed zone of inhibition in the range 25 to 30 mm. Percentage of inhibition of DPPH radical scavenging activity by methanolic leaves extract of Casiatica showed higher value which were 38.53% for 1.25 mg/ml, 30.35% for 2.5 mg/ml, 84.55% for 5 mg/ml, 85.16% for 10 mg/ml and 86.47% for 20 mg/ml while the methanolic roots extract of Casiatica were 10.38% for 1.25 mg/ml, 4.35% for 2.5 mg/ml, 14.52% for 5 mg/ml, 62.26% for 10 mg/ml and 79.32% for 20 mg/m!. In conclusion, the CenteUa asiatica leaves extract showed greater antimicrobial and antioxidant activities compared with the roots. In vivo study is highly recommended for further study.